2002
DOI: 10.1097/00007890-200206150-00020
|View full text |Cite
|
Sign up to set email alerts
|

Liver repopulation after cell transplantation in mice treated with retrorsine and carbon tetrachloride1

Abstract: This murine study demonstrates high levels of repopulation after liver cell transplantation into nongenetically modified livers, using a cell cycle inhibitor and chemical liver injury to provide transplanted cells a proliferative advantage. Liver repopulation was effected mostly by a small fraction of transplanted cells. Analogous nonsurgical liver cell transplantation strategies, but with clinically applicable drugs, could be devised for the treatment of liver-based metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 22 publications
2
58
0
Order By: Relevance
“…Retrorsine and CCl 4 stock solutions were prepared as described previously (Guo et al 2002). Before injection, retrorsine stock solution was diluted 1:5 in sterile PBS.…”
Section: Conditioning Of Recipient Mice and Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrorsine and CCl 4 stock solutions were prepared as described previously (Guo et al 2002). Before injection, retrorsine stock solution was diluted 1:5 in sterile PBS.…”
Section: Conditioning Of Recipient Mice and Transplantationmentioning
confidence: 99%
“…All these approaches share the feature that hepatocytes are transplanted into a predamaged liver which provides a regenerative environment for transplanted cells (Shafritz and Dabeva 2002;Dabeva and Shafritz 2003). Recently, Guo et al (2002) reported an enhanced repopulation of the mouse liver after pretreatment of the animals with retrorsine. Retrorsine is an alkaloid that exerts a strong and persistent block of native hepatocyte proliferation (Laconi et al 1999).…”
Section: Intrahepatic Seeding Of Genetically Modified Liver Progenitomentioning
confidence: 99%
“…Despite a short half life period, retrorsine may suppress hepatocyte proliferation for weeks and even months [24] . Retrorsine mainly blocks phases S and G2 of the liver cell cycle; that is, it blocks cell mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]67,88 To apply this principle to most liver disorders, in which host diseased hepatocytes could compete with donor hepatocytes for liver repopulation, animals were pretreated with retrorsine or subjected to whole liver irradiation to inhibit proliferation ability of host hepatocytes before cell transplantation. 85,89,90 In combination with a strong regenerative pressure (eg twothirds partial hepatectomy, thyroid hormone administration, ischemia-reperfusion injury or FasL gene transfer), a nearly complete repopulation of host liver by donor hepatocytes was obtained after transplantation of 0.5% of the recipient liver mass. 89,[91][92][93] Similarly, lentivirally transduced hepatocytes were massively expanded in retrorsine/partial hepatectomy-treated rats.…”
Section: Strategies For Liver Repopulationmentioning
confidence: 99%